Postcranial morphology of Aristonectes Cabrera (Plesiosauria, Elasmosauridae) from the Upper Cretaceous of Patagonia and Antartica - O'gorman, Jose Patricio; Brandoni, Zulma Nelida; Salgado, Leonardo (Antarctic Science)
A partial, postcranial skeleton of a juvenile individual referred to Aristonectes cf. parvidens from the upper Maastrichtian Lo´pez de Bertodano Formation, Isla Marambio (Seymour Island), Antarctica, is described. Additionally, two juvenile specimens, also referred to A. cf. parvidens from the Allen Formation (upper Campanian–lower Maastrichtian) and Jagu¨el Formation (upper Maastrichtian) (Rı´o Negro province, Argentina), are redescribed. The analysis of the systematic value of the cervical centrum proportions of juvenile specimens of Elasmosauridae suggests that these elements can be used to differentiate juvenile specimens of A. cf. parvidens from juveniles of other Elasmosauridae. On this basis, the specimens described are referred to A. cf. parvidens. Based on the proportion of the cervical centra, the first South American plesiosaur described by Gay in 1848 is here referred to A. cf. parvidens. The coracoid of Aristonectes is described for the first time showing a cordiform fenestra, a feature only recorded in the Elasmosauridae among the Plesiosauria, therefore, these new data support the inclusion of Aristonectes within the Elasmosauridae. With the new material described in this paper, Aristonectes is one of the most frecuently recorded genera of Late Cretaceous plesiosaurs in the Southern Hemisphere. Fil: O'gorman, Jose Patricio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Brandoni, Zulma Nelida. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Salgado, Leonardo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Rio Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiologia y Geologia; Argentina